2007
DOI: 10.1007/s00277-007-0391-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of bronchoscopy with bronchoalveolar lavage in febrile patients with hematologic malignancies and pulmonary infiltrates

Abstract: Infectious complications are a major cause of morbidity and mortality in immunosuppressed patients. Febrile patients with hematologic malignancies and pulmonary infiltrates have high mortality rates, especially if mechanical ventilation is required. The diagnostic value of fiberoptic bronchoscopy (FOB) with bronchoalveolar lavage (BAL) in these patients is controversial. We retrospectively analyzed the microbiological results of BAL samples obtained during 249 FOB examinations from 199 febrile patients with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 29 publications
3
74
0
Order By: Relevance
“…Azoulay et al [2] even demonstrated that in critically ill hematological and oncological patients with acute respiratory failure, non-invasive strategies had a higher diagnostic yield than bronchoscopy and BAL. On the other hand, the studies of Dunagan et al [8], Hummel et al [14], and Peikert et al [21] were in favor for the application of BAL in immunocompromised patients. They stated good diagnostic yield and frequent therapeutic implications in more than 50% of patients, although an impact on survival could not be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Azoulay et al [2] even demonstrated that in critically ill hematological and oncological patients with acute respiratory failure, non-invasive strategies had a higher diagnostic yield than bronchoscopy and BAL. On the other hand, the studies of Dunagan et al [8], Hummel et al [14], and Peikert et al [21] were in favor for the application of BAL in immunocompromised patients. They stated good diagnostic yield and frequent therapeutic implications in more than 50% of patients, although an impact on survival could not be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…There exist some data that support a frequent use of BAL in immunocompromised patients with pulmonary infiltrates [8,14,21]. But, especially in severely ill patients with neutropenia, BAL is associated with a high rate of complications [2,11,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large recent study has supported the role of BAL in the assessment of such patients, it did not assess the clinical benefit following BAL or report on complications other than death (Hummel et al, 2008). It also failed to state the type of antimicrobial agents used in the study, and these may have changed over the 15-year study period.…”
mentioning
confidence: 99%
“…12,[16][17][18] The treatment modification rate was higher in our study compared to other studies. Among patients in whom treatment was modified, those in whom antibiotic were changed as per culture sensitivity pattern showed maximum clinical improvement with 90%, followed by those in whom anti tuberculosis treatment was started showed 70% improvement and those in whom antifungals were started 60% clinical improvement.…”
Section: Discussionmentioning
confidence: 50%